Integration of ESG and Sharia Principles in Sri Sukuk: Challenges and Opportunities Towards a Sustainable Financial System - Dewi, Ratna Sari; Hidayat, Toni; Munawarah (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2025)
This study aims to analyze the challenges and strategic opportunities for developing SRI Sukuk to support the sustainability of the Islamic financial system in Indonesia. The research method uses a descriptive qualitative approach with literature analysis of reputable international journals and national journals accredited by Sinta 1 and 2. The results show that although SRI Sukuk faces several challenges, such as limited global standards, low investor literacy, high certification costs, and a lack of social impact indicators, there are significant strategic opportunities. These opportunities include regulatory and public policy support, increasing demand from global institutional investors, synergy with the SDGs agenda and the Indonesian Islamic Economic Masterplan, the adoption of digital technology and Islamic fintech, and increasing sustainable financial literacy. This study concludes that SRI Sukuk has the potential to be a key driver of the transformation of the Islamic financial system towards green finance that is inclusive, transparent, and oriented towards the welfare of the people